Junkie Land sebuah ungkapan visual tentang negeri impian - Daud Mahagni Kama Adhi (Saraswati)
Fine art is a tool to communicate feelings and ideas. In some ways, all the artwork functions as a medium of personal expression of an artist, but too as a personal tool of expression, art can not be limited by his own inspiration or experience alone. Art can also talk about the personal view of the events that were happening at that time and common familiar objects from the author’s, constant events such as death, the celebration of something, parting, meeting and so forth. Art is an expression of the psychological dimensions of life. Quoting the words of Edmund Burke Feldman translated by SP. Gustami titled Art As Image and Idea, "The artist does not merely involve themselves with issues specific person, but rather to comment on the issue of universal." Similarly what will be visualized from the author's childhood story about the state of peace, calm, peaceful, comfortable and safe. All these ideas and concepts will be visualized through graphic art techniques such as silkscreen print and relief print. The artwork is not born out of a vacuum. "Junkie Land" is a writer’s expectancy about life in this country are run on the basis of peace and comfort together. "Work of art is an expression of perception and aesthetic impressions. An artist, creating works of art, when he managed to freeze moments aesthetic that happened to him. "Junkie Land is a land of imagination about the beautiful country and will always make addicted people who come there. As Indonesia's rich agricultural and tradition as well as the value of local knowledge, hospitality that will always make people addicted to come visit, and come again. The term "Junkie Land" of the authors do not appear out of nowhere, this term appears not to make such a negative stigma from the word meaning "Junkie" itself which means addicts, and not to damage the image of  Indonesian nation, but this term is explained to a land of dreams concept of  the ideal condition and balance, the author land of dreams imagine over the years.